Glee. The complete first season [videorecording (DVD)]. - Michele, Lea; Monteith, Cory, 1982-2013; Gilsig, Jessalyn, 1971-; Lynch, Jane, 1960- (20th Century Fox Home Entertainment, 2010)
This musical release from the explosively popular comedy-drama GLEE includes all 22 episodes of the show's first season, following the William McKinley High School Glee Club and its inspirational director Will Scheuster as they navigate cliques, love triangles, pregnancies - both real and fake - and more, all while working on show stopping renditions of contemporary songs.